Cardiac myxoma and its growth over 5 years in a patient with a history of multiple cerebrovascular events: a case report - Martinez, Viviana A.; Blanco, Joaquín; López, Vanesa; Ramos, Bryan S.; Scull, Lorena; Godínez, David; Braga, Jarred F. (International Journal of Research in Medical Sciences, 2025)
Cardiac tumors frequently present significant clinical, diagnostic, and therapeutic challenges. In many cases, a cardiac mass is detected incidentally and can represent benign or malignant processes, primary or secondary. Over 90% of primary cardiac tumors are benign (in adults, myxomas are most common, while in children, rhabdomyomas are more frequent). These tumors can be further classified as simple or complex based on the necessary treatment and may affect different chambers of the heart and the pericardium. Secondary or metastatic cardiac tumors are 30 times more common than primary neoplasms, with an incidence in autopsies ranging from 1.4% to 14%. Myxomas constitute approximately 50% of all benign cardiac tumors in adults. Most myxomas (over 80%) are located in the left atrium, with decreasing frequency in the right atrium, right ventricle, and left ventricle. We present the case of a 76-year-old woman who was found to have a left atrial mass identified on echocardiogram in 2019 as part of a cerebrovascular disease evaluation protocol. However, the patient did not attend follow-up. In December 2024, she was hospitalized for a lower respiratory tract infection, and during her admission, a new echocardiographic study showed tumor growth over 5 years.